Efektivitas Promosi Produk Chatime Melalui Instagram Menggunakan Model AIDA - Tasya Rizki Nur Ofifah; Agung Kresnamurti Rivai P; Nofriska Krissanya (Univiversitas Dr. Djar Wattiheluw, 2023)
This study aims to determine the extent of Chatime's effectiveness when evaluated with the AIDA model. This research uses a case study method with a qualitative approach with data collection through interviews, documentation, and observation. The informants in this study were 10 key informants who were followers of Chatime Instagram. The results showed that Chatime's promotional efforts were in accordance with the attention and desire stages in the AIDA model, but were still lacking in reaching the interest and action stages.